Statistical Analysis Selector - Rahman, Muhammad Akram; Jaapar, Aini; Wan Mohd Zain, Wan Zuraida; Mahdzar, Mazlina; Abd Rahim, Shahril Azwan (Multidisciplinary Applied Research and Innovation, 2021)
Pejabat Program Pra Pendidikan Tinggi (PPT) UiTM is an office that concentrates on programs that enhance students’ education at the pre-diploma level, which enables them to get entries into Diploma programs. Thus, students’ data play an important role for the office to make decisions that can benefit the students. Since the statistical analysis has been important in decision making, but no one with a permanent role at the office has a strong Statistics background. It can be quite cumbersome for anyone in the office to find appropriate statistical analysis that can serve office business requirements. A software application was innovated to make effective decision making in suggesting some statistical analysis which can be appropriately done based on given data input. End users will have to input a dataset and then a list of variables can be chosen for analysis. Next, a few analyses will be given to be chosen from and the end-users will get the outcomes that are required. Technically, the app can help to simplify the analysis process by checking the statistical analysis. Then, it can give a list of suitable analysis can be picked from and thus results can be obtained in a short time. Agile methodology concept was carried out which briefly involved of technical analysis plan and design phase for fulfilling conditional requirements between statistical analysis and application utilities, application development phase for building the application, and finally evaluation phase for the app to be assessed by PPT officers. With this innovation, there will be less headache and time consumption on exploring and doing some research about many statistical methods that will not even be used. Thus, PPT officers of non-Statistics background have no need to do any research on statistical analysis, but necessary outcomes of business objectives can be attained from the software application.